Images of thought visuality in Islamic India 1550-1750 - Minissale, Gregory (Cambridge Scholars Press, 2006)
Images of Thought is an entirely new approach to understanding non-Western art. Supported by a wide reading in anthropology, theology and philosophy, it provides an intellectual context for reading the visual language of Indian and Persian miniature art. By decoding artistic conventions, and with searching visual analyses, the book attempts to transform our understanding of art as an illustration of history to art as a reflection of the intellect. Images of Thought should be of interest to the general reader, students and sholars of art and crirtical theory, as it shows that one of the world's richest painting traditions can offer important insights into issues of visual perception and intellectual production generally.